Optimization of transmission signal by artificial intelligent - Hassan Farahan Rashag; Mohammed H. Ali (International Journal of Advances in Applied Sciences, 2019)
In this method, radial basis function network RBFNN is an artificial intelligent which is used to identify and classify the communication system performance.  RBFNN is one type of neural network which has activation functions. It consists of three layer input layer, hidden layer and output linear combination. One of the main problems of communication system is that it causes slow response for sending signal via the transmission devices. Therefore, the artificial intelligent by RBFNN is used to optimize the transmission signal. The input signal is trained and testing by neurons with weight and this lead to provide linear output. The simulation results have the optimization specifics over the traditional communication transmission devices.